Double modals in Australian and New Zealand English - Morin, Cameron; Coats, Steven (World Englishes, 2025)
This paper reports the first large‐scale corpus study of double modal usage in Australian and New Zealand Englishes, based on a multi‐million‐word corpus of geolocated automatic speech recognition transcripts from YouTube. Double modals are considered rare grammatical features of English, which have long been extremely difficult to observe in natural language due to low frequencies, non‐standardness, and restriction to oral speech registers. In addition, it has generally been assumed that they make up small sets of diachronically related forms, whose geographical distribution is mainly restricted to the Southern US and the North of the UK. Our results challenge these long‐standing assumptions by presenting the first inventory of double modals observed outside of these regions, thanks to computational sociolinguistic methods. Overall, we identify and map 474 double modal tokens distributed in 51 types, an unexpectedly large collection of forms used with varying frequencies across Australia and New Zealand. We consider the relevance of our results for three specific new claims concerning the diversity, complexity, and origins of double modals in English world‐wide.